Will transaction costs and economies of scale tip the balance in farm size in industrial agriculture? An illustration for non-food biomass production in Germany - Lanjiao Wen; Lioudmila Chatalova (Sustainability, 2021)
The study investigates how the agricultural sector can respond to a growing non-food biomass demand. Taking Germany as an example, a stylized case of biomass production under conditions of technological advance and constantly growing demand is modelled. It is argued that biomass producers might seek to adjust their farm size by simultaneously optimizing benefits from the production scale and transaction cost savings, where transaction costs are measured using Data Envelopment Analysis. The results extend the debate on transaction costs and structural change in agriculture by revealing a possible synergy and trade-off between transaction cost savings and benefits from (dis)economies of scale. They show that if larger farms cannot economize on transaction costs, then investments in land and labor, needed to adjust to higher biomass demand, partly compromise the returns to scale, which decelerates the farm size growth. A higher degree of asset specificity gives rise to transaction costs and reduces the rate at which the farm size decreases. Smaller producers may disproportionally benefit from their higher potential of transaction cost savings, if advanced technologies can offset the scale advantage of larger farms. The findings inform policymakers to consider this complex effect when comparing the opportunities of smaller and larger agricultural producers in the bioeconomy.
Keywords: 330; agricultural biomass; Data Envelopment Analysis; economies of scale; Germany; optimal farm size; transaction costs